Repeat expansions nested within tandem CNVs: a unique structural change in GLS exemplifies the diagnostic challenges of non-coding pathogenic variation. Issue 1 (1st August 2022) - Fazal, Sarah; Danzi, Matt C; van Kuilenburg, André B P; Reich, Selina; Traschütz, Andreas; Bender, Benjamin; Leen, René; Toro, Camilo; Usdin, Karen; Hayward, Bruce; Adams, David R; van Karnebeek, Clara D M; et al.
Abstract: Glutaminase deficiency has recently been associated with ataxia and developmental delay due to repeat expansions in the 5′UTR of the glutaminase ( GLS ) gene. Patients with the described GLS repeat expansion may indeed remain undiagnosed due to the rarity of this variant, the challenge of its detection and the recency of its discovery. In this study, we combined advanced bioinformatics screening of ~3000 genomes and ~1500 exomes with optical genome mapping and long-read sequencing for confirmation studies. We identified two GLS families, previously intensely and unsuccessfully analyzed. One family carries an unusual and complex structural change involving a homozygous repeat expansion nested within a quadruplication event in the 5′UTR of GLS . Glutaminase deficiency and its metabolic consequences were validated by in-depth biochemical analysis. The identified GLS patients showed progressive early-onset ataxia, cognitive deficits, pyramidal tract damage and optic atrophy, thus demonstrating susceptibility of several specific neuron populations to glutaminase deficiency. This large-scale screening study demonstrates the ability of bioinformatics analysis—validated by latest state-of-the-art technologies (optical genome mapping and long-read sequencing)—to effectively flag complex repeat expansions using short-read datasets and thus facilitate diagnosis of ultra-rare disorders.